Pengaruh Tingkat Hutang, Fee Audit Dan Konsentrasi Pasar Terhadap Persistensi Laba: Firm Age Sebagai Variabel Moderasi - Afifah, Siti; Yunita, Khristina; Hamzani, Umiaty; Desyana, Gita; Indah, Djunita Permata (Fakultas Ekonomi Prodi Akuntansi, 2024)
The purpose of this study is to examine the effect of debt levels, audit fees, and market concentration on earnings persistence, and to analyze whether firm age is able to strengthen the relationship between debt levels, audit fees, and market concentration on earnings persistence in transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The novelty of this study lies in the object of research and the use of firm age as a moderating variable that has not been widely studied. The population of the study was 37 companies with a research sample of 8 companies selected using purposive sampling techniques. This study uses a quantitative method using multiple linear regression analysis techniques and moderated regression, and the analysis tool is SPSS 23 software. The findings of this study indicate that debt levels have a negative and significant effect on earnings persistence, while audit fees do not affect earnings persistence and market concentration has a positive and significant effect on earnings persistence. Firm age is only able to negatively weaken the relationship between audit fees and earnings persistence, but is unable to strengthen the relationship between debt levels and market concentration with earnings persistence. Simultaneously, debt levels, audit fees and market concentration affect earnings persistence.